Effect of prior instructions on preprogrammed reactions of trunk muscles in individuals with and without chronic low back pain - Shenoy, Sh.; Balachander, H.; Sandhu, J.S. (Нейрофизиология, 2014)
The late component of the stretch reflex occurring in humans within a 40 to 120 msec interval
following a loading perturbation is qualified as a preprogrammed muscle reaction (PPR).
The PPR size can be significantly modulated with prior instructions. These modifications
are significantly influenced by a number of factors, in particular by the presence of pain
syndromes. The objective of our study was to compare the effect of prior instructions on
the PPR amplitude in the trunk muscles in individuals with chronic low back pain (LBP)
compared to healthy controls. LBP is a widespread syndrome, especially in athletes. Surface
EMGs were recorded from superficial trunk muscles, rectus abdominis (RA) and erector
spinae (ES), in athletes suffering from chronic LBP (n = 24) and asymptomatic (healthy)
athletes (n = 25). Loading perturbations (induced by dropping a weight, application of 3 kg
force, ≈ 30 N, to the outstretched hand from a 8 cm height) were introduced in standing at
a known time with prior instructions to “let go” for the induced perturbation or to “resist”
it. The root mean square (RMS) of the EMG amplitudes within the reaction duration were
compared between the two groups. Statistically significant differences were obtained when
the mean PPR EMG amplitudes were compared between the LBP and control groups for
the above two task instructions; this was found for both examined muscles, RA and ES
(P < 0.05). Therefore, individuals with chronic LBP exhibit poorly modulated PPR amplitudes
according to prior task instructions. Changes in the networks controlling automatically
regulated movements and excitability of the spinal pathways could be responsible for this
specificity Пізній компонент стретч-рефлексу, що розвивається у людей в інтервалі 40–120 мс після пертурбації (навантаження), кваліфікується як м’язова препрограмована реакція
(ППР). Величина ППР може істотно модулюватися під дією
попередніх інструкцій. На ці модифікації істотно впливають численні фактори, зокрема наявність больових синдромів. Ціллю нашого дослідження було порівняння амплітуд
ППР м’язів тулуба в осіб, що страждали на біль у попереку
(БП), та здорових контрольних тестованих. БП є виключно широко розповсюдженим синдромом, особливо у спортсменів. Ми відводили ЕМГ від поверхневих м’язів тулуба –
rectus abdominis (RA) та erectror spinae (ES) – у спортсменів із синдромом хронічного БП (n = 24) та спортсменів без такого розладу (здорових, n = 25). Силові пертурбації (прикладання ваги 3 кгс до витягнутої руки з висоти
8 см) вводились у певний момент до тестованого в положенні стоячи з попередніми інструкціями «не опиратися»
введеному навантаженню або «опиратися» йому. Порівнювалися значення RMS для амплітуд ЕМГ у межах реакції,
що спостерігалася в двох групах. Було виявлено, що середні амплітуди ППР-ЕМГ у групах БП та контролю при двох
вказаних вище попередніх інструкціях вірогідно відрізнялися; це було властиве для обох обстежених м’язів – RA та ES
(P < 0.05). Таким чином, особи, що страждають на хронічний БП, демонструють обмежену модуляцію амплітуди ППР
відповідно до попередніх інструкцій. Зміни в нейронних мережах, що контролюють автоматично регульовані рухи та
збудливість спінальних шляхів, вірогідно є відповідальними за таку специфіку.